Penerapan Tools Fail2Ban Untuk Mencegah Serangan Brute Force Pada Web Server Online Learning Uhamka (OLU) - Yustika Ramadhani; Muchammad Sholeh (UHAMKA Press, 2022)
This study aims to assist the internal team of BPTI UHAMKA in making the Online Learning UHAMKA (OLU) web server so that the login credentials of the UHAMKA academic community are protected from attempted brute force attacks. Fail2Ban is a server security tool where it detects login attempts according to the maximum pre-configured trial value. In its implementation, Fail2Ban which uses the python programming language is installed on the Online Learning UHAMKA (OLU) server that uses the CentOS 7 server operating system. In the way it works, Fail2Ban will block or ban IP addresses that try to log in consecutively within one hour. Based on the comparison before and before its implementation, it can be proven that Fail2Ban can detect brute force attacks that occur and ban the attacker's IP address.